Muhammad al-Idrisi Father of Modern Geography and Maps! - Haque, Anwar Ul (International Journal of Pathology, 2018)
Abu Abd Allah Muhammad al-Idrisi al-Qurtubi al-Hasanial-Sabti commonly known as Al Idrisi was a great Muslimgeographer, cartographer and traveler could be rightly calledas the father of modern Geography and Maps! He belongedto an era when Great Muslim Empire had suffered from declineand had shown some cracks due to their drifting awayfrom Quran. He was born in Ceuta, where his greatgrandfatherhad been forced to settle after the fallof Hammudid Malaga to the Zirids of Granada. He spentmuch of his early life travelling through North Africaand Al-Andalus and seems to have acquired detailed informationon both regions. He visited Anatolia when he wasbarely 16. He is known to have studied in CórdobaApparently his travels took him to many parts of Europeincluding Portugal, the Pyrenees, the French Atlantic coastHungary, and Jórvík also known as York, in England. LikeMuslim geographers before him, Al-Idrisi traveled manydistant places, including Europe, to gather geographical data.The Muslim geographers had already made accuratemeasurements of the earth's surface, and several maps of thewhole world were available. Al-Idrisi combined this availableknowledge with his own findings to create comprehensiveinformation for all parts of the known world. As hisfame spread, he gained the attention of European sea navigatorsand military planners and eventually that of Roger II,the Norman King of Sicily, who invited him to produce anup-to-date world map.